Interaction between circadian rhythms and stress - Koch, C.E. (Neurobiol Stress, 2016)
Life on earth has adapted to the day-night cycle by evolution of internal, so-called circadian clocks that adjust behavior and physiology to the recurring changes in environmental conditions. In mammals, a master pacemaker located in the suprachiasmatic nucleus (SCN) of the hypothalamus receives environmental light information and synchronizes peripheral tissues and central non-SCN clocks to geophysical time. Regulatory systems such as the hypothalamus-pituitary-adrenal (HPA) axis and the autonomic nervous system (ANS), both being important for the regulation of stress responses, receive strong circadian input. In this review, we summarize the interaction of circadian and stress systems and the resulting physiological and pathophysiological consequences. Finally, we critically discuss the relevance of rodent stress studies for humans, addressing complications of translational approaches and offering strategies to optimize animal studies from a chronobiological perspective.